Content, Commerce, and Community Effects on TikTok Live Engagement - Edigani Putra, Mohammad Alaric Hanedhy; Aruman, Akhmad Edhy; Valentino, Raynaldi Samuel; Edigani Putra, Mohammad Bayu (Communicare : Journal of Communication Studies, 2025)
The rapid growth of TikTok as a social commerce platform has transformed how brands engage with consumers through live-streaming features. Although prior studies have examined content, commerce, and community individually, limited research has explored their integrated and synergistic effects on consumer engagement in real-time digital environments, particularly within the Indonesian beauty industry. This study addresses this gap by applying the Content, Commerce, and Community (3C) framework to examine the collective influence of these dimensions on engagement during TikTok Live sessions. Using a quantitative approach, data were collected through an online questionnaire distributed to users who had interacted with Make Over Indonesia’s TikTok Live content. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that content, commerce, and community have significant positive effects on consumer engagement. Among these factors, commerce emerges as the strongest determinant, highlighting the critical role of transactional convenience and real-time shopping features in live-streaming commerce. These results underscore the importance of integrating engaging content, seamless commerce functionalities, and interactive community elements to enhance consumer engagement in social commerce settings. This study contributes to the empirical development of the 3C framework and offers practical insights for marketers seeking to optimize engagement strategies on live-streaming platforms.